Acyl dihydropyrazolo[1, 5-a]pyrimidinones as metabotropic glutamate receptor 5 positive allosteric modulators. Issue 22 (15th November 2015) - Malosh, Chrysa; Turlington, Mark; Bridges, Thomas M.; Rook, Jerri M.; Noetzel, Meredith J.; Vinson, Paige N.; Steckler, Thomas; Lavreysen, Hilde; Mackie, Claire; Bartolomé-Nebreda, José M.; Conde-Ceide, Susana; Martínez-Viturro, Carlos M.; et al.
Graphical abstract: Abstract: We report the optimization of a series of metabotropic glutamate receptor 5 (mGlu5 ) positive allosteric modulators (PAMs) from an acyl dihydropyrazolo[1, 5- a ]pyrimidinone class. Investigation of exocyclic amide transpositions with this unique 5, 6-bicyclic core were conducted in attempt to modulate physicochemical properties and identify a suitable backup candidate with a reduced half-life. A potent and selective PAM, 1-(2-(phenoxymethyl)-6, 7-dihydropyrazolo[1, 5- a ]pyrimidin-4(5 H )-yl)ethanone (9a, VU0462807), was identified with superior solubility and efficacy in the acute amphetamine-induced hyperlocomotion (AHL) rat model with a minimum effective dose of 3 mg/kg. Attempts to mitigate oxidative metabolism of the western phenoxy of9a through extensive modification and profiling are described.